2005
DOI: 10.1523/jneurosci.1019-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Vesicle-Mediated Transport and Release of CCL21 in Endangered Neurons: A Possible Explanation for Microglia Activation Remote from a Primary Lesion

Abstract: Whenever neurons in the CNS are injured, microglia become activated. In addition to local activation, microglia remote from the primary lesion site are stimulated. Because this so-called secondary activation of microglia is instrumental for long-term changes after neuronal injury, it is important to understand how microglia activity is controlled. The remote activation of microglia implies that the activating signals are transported along neuronal projections. However, the identity of these signals has not yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
117
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(131 citation statements)
references
References 62 publications
14
117
0
Order By: Relevance
“…Cortical neurons were prepared from embryonic mouse brains (E15-16) as described before (de Jong et al, 2005). Neurons were used after 6 days in culture.…”
Section: Primary Neuronal Culturesmentioning
confidence: 99%
“…Cortical neurons were prepared from embryonic mouse brains (E15-16) as described before (de Jong et al, 2005). Neurons were used after 6 days in culture.…”
Section: Primary Neuronal Culturesmentioning
confidence: 99%
“…Neuronal cysteine-cysteine chemokine ligand 21 (CCL21) is synthesized by damaged neurons; following packaging in vesicles and transport, it reaches presynaptic sites, where it is released to activate microglia at sites distant from the primary lesion. [72][73][74][75] Spinal cord contusion injury at T9 increases CCL21 signal in excitatory neurons of the dorsal horn and in spinal parenchyma at both the T9 and L4 spinal segments. 54 Distal release of CCL21 produced following SCI by injured neurons at the trauma site has been proposed as a molecular mechanism that triggers microglial activation at spinal segments far from the site of injury, and in the thalamus in association with pain phenomena.…”
Section: Disrupted Brain Neurogenesis/er Stress Aftermentioning
confidence: 99%
“…Significant advances have been made towards understanding how injury to a nerve signals to the dorsal horn causing increased P2X4R expression in microglia. One such neuronmicroglia signaling molecule is CCL21, a microglia-activating chemokine released from injured neurons [5,20]. A recent study by Biber et al [5] reported that following injury to a peripheral nerve, CCL21 expression was significantly increased in small diameter neurons in the dorsal root ganglia and in primary afferent nerve terminals in the spinal dorsal horn, but not in microglia or in astrocytes.…”
Section: Introductionmentioning
confidence: 99%